A reactive hybrid product-driven system for rescheduling in a manufacturing planning - Patricio Sáez Bustos; Victor Parada Daza (Brazilian Journal of Operations & Production Management)
Goal: This research aims to develop a novel scheduling model integrating the intelligent product paradigm of a product-driven system (PDS) with the shifting bottleneck heuristic (SBH) to enhance rescheduling efficiency and adaptability in dynamic job shop scheduling problems with disruptions (JSSP-D).